Local INR correction: justification for a simplified approach. Issue 9 (September 1997) - Craig, S; Stevenson, K J; Dufty, J M; Taberner, D A
Abstract : AIMS: Errors in reporting International Normalised Ratios (INR) may be corrected by assignment of a System International Sensitivity Index (System ISI). This 57 centre study tests the validity of several procedures for INR correction. METHODS: Prothrombin times of eight lyophilised coumarin calibrants, a lyophilised normal pool calibrant, and eight frozen coumarin plasmas were determined at each centre. The calibrants were calibrated using international reference preparations. The eight frozen coumarin plasmas were calibrated in a four centre international exercise. The relations tested were: (a) the logarithm of local prothrombin time against the logarithm of reference prothrombin time; (b) reference INR against local prothrombin time; and (c) logarithm of reference INR against logarithm of local prothrombin time. These methods were analysed by both linear and orthogonal regression. RESULTS: All system groups required correction, the mean percentage deviation of the uncorrected data from the calibrated values was 19.0%. There was also considerable variation in INR, with the coefficient of variance (CV) ranging from 11.30 to 17.29%. Correction of INR was possible with all methods (CV reduced to < 7%). However, only when a plot of the logarithm of local prothrombin time against the logarithm of reference prothrombin time was fitted by orthogonal regression, or a plot of logarithm of reference INR against logarithm of local prothrombin time was fitted by either type of regression analysis, did the best fit line through the calibrant plasmas also pass close to the local mean normal prothrombin time. CONCLUSIONS: While INR correction may be achieved by all the above methods, that relating log reference INR to log local prothrombin time by linear regression analysis is the simplest to perform.